Metal ion adsorption at the ionic liquid–mica interface. Issue 2 (10th December 2015) - McDonald, Samila; Elbourne, Aaron; Warr, Gregory G.; Atkin, Rob
Abstract : Metal ion adsorption at ionic liquid–mica interfaces has been elucidated using AM-AFM imaging. Abstract : Mica has been employed in many studies of ionic liquid (IL) interfaces on account of its atomic smoothness and well defined surface properties. However, until now it has been unclear whether ions dissolved in ILs can compete with the IL cation and adsorb to mica charge sites. In this work amplitude modulated atomic force microscopy (AM-AFM) has been used to probe metal ion adsorption at the interface of mica with propylammonium nitrate (PAN), a room temperature IL. Lithium, sodium, potassium, magnesium and calcium nitrate salts were added to PAN at a concentration of ∼60 mM. Aluminum nitrate was also investigated, but only at 5 mM because its solubility in PAN is much lower. The AM-AFM images obtained when the metal ions were present are strikingly different to that of pure PAN, indicating that the ions compete effectively with the propylammonium cation and adsorb to negatively charged sites on the mica surface despite their much lower concentration. This is a consequence of electrostatic attractions between the mica charge sites and the metal ions being significantly stronger than for the propylammonium cation; compared to the metal ions the propylammonium charged group is relatively constrained sterically. A distinct honeycomb pattern is noted for the PAN + Al 3+ system, less obviously for the divalent ions and not at all for monovalent ions. This difference is attributed to the strength of electrostatic interactions between metal ions and mica charge sites increasing with the ion charge, which means that divalent and (particularly) trivalent ions are located more precisely above the charged sites of the mica lattice. The images obtained allow important distinctions between metal ion adsorption at mica–water and mica–PAN interfaces to be made.